Decision Support System Model for PPPK Teacher Selection Using the AHP Method - Adinda Fadilah Hamdi; Refliana Refliana (Jurnal Riset Ilmu Teknik, 2024)
This study to develop a decision support system based on the Analytical Hierarchy Process (AHP) in the recruitment process of Government Employees with Work Agreements (PPPK) at SMP Negeri 1 Ukui. The background of this study is the need for a more objective, transparent, and accountable selection mechanism to reduce subjectivity in determining the passing grade for honorary teachers. The research method used a descriptive quantitative approach with data collection through observation, interviews, and paired comparison questionnaires administered to the principal, senior teachers, administrative staff, and school supervisors. The results of the analysis show that the Administration criterion received the highest weight (0.343), followed by Suitability Selection (0.535) and Interviews (0.122). In the subcriteria, the aspect of administrative document filing was the dominant factor (48%), while in suitability selection, teacher performance ranked highest (39%). Sensitivity analysis proved that the ranking results of teacher candidates were relatively stable even though the criteria weights changed. These findings confirm that AHP can minimize the subjectivity of selection and provide a quantitative basis for determining candidate priorities. This study has implications for improving the accountability of PPPK recruitment policies at the school level while opening up opportunities for the integration of hybrid methods such as AHP–TOPSIS in future research.